2006
DOI: 10.1016/j.biomaterials.2006.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of poly(anhydride-esters) into non-steroidal anti-inflammatory drugs and their effect on Pseudomonas aeruginosa biofilms in vitro and on the foreign-body response in vivo

Abstract: The ability of poly(anhydride-esters) composed of non-steroidal anti-inflammatory drugs that biodegrade to salicylic acid (SA) and adipic acid to prevent colonization by Pseudomonas aeruginosa and their effects on the foreign-body response were studied in vitro and in vivo, respectively. Soluble SA in bacterial medium at concentrations up to 300 mg/L did not affect the growth rate or viability of P. aeruginosa, indicating that SA does not exhibit a direct toxicity effect on the bacterium. Batch degradation rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 30 publications
1
56
0
Order By: Relevance
“…Some microorganisms are reported to change their morphology (e.g., Bacillus subtilis, Caulobacter crescentus) under harsh conditions, which allows them to exist in a hostile environment (O'Toole et al 2000). In the initial stage, microorganisms produce some proteins such as collagen, fibrin, fibronectin and laminin as a coating material, which help in cell-to-cell adhesion in biofilm (Bryers et al 2006;Simoes et al 2010). Biofilms exist as a matrix of extracellular polymeric substance (EPS) that depends on the surrounding conditions; it consists of a series of biological and physical changes during matrix formation and from the three-dimensional structure (Prakash et al 2003;Bryers et al 2006;Simoes et al 2010).…”
Section: Microbial Development As Biofilms On Polymermentioning
confidence: 99%
See 1 more Smart Citation
“…Some microorganisms are reported to change their morphology (e.g., Bacillus subtilis, Caulobacter crescentus) under harsh conditions, which allows them to exist in a hostile environment (O'Toole et al 2000). In the initial stage, microorganisms produce some proteins such as collagen, fibrin, fibronectin and laminin as a coating material, which help in cell-to-cell adhesion in biofilm (Bryers et al 2006;Simoes et al 2010). Biofilms exist as a matrix of extracellular polymeric substance (EPS) that depends on the surrounding conditions; it consists of a series of biological and physical changes during matrix formation and from the three-dimensional structure (Prakash et al 2003;Bryers et al 2006;Simoes et al 2010).…”
Section: Microbial Development As Biofilms On Polymermentioning
confidence: 99%
“…In the initial stage, microorganisms produce some proteins such as collagen, fibrin, fibronectin and laminin as a coating material, which help in cell-to-cell adhesion in biofilm (Bryers et al 2006;Simoes et al 2010). Biofilms exist as a matrix of extracellular polymeric substance (EPS) that depends on the surrounding conditions; it consists of a series of biological and physical changes during matrix formation and from the three-dimensional structure (Prakash et al 2003;Bryers et al 2006;Simoes et al 2010). (Gu 2003) Microbial species grow on a wide variety of surfaces, i.e., inert or living.…”
Section: Microbial Development As Biofilms On Polymermentioning
confidence: 99%
“…Furthermore, effect of media on degradation rate was studied and found to increase marginally better (14%) in media containing actively growing bacterial culture than sterile media. A signifi cant reduction in formation of Pseudomonas aeruginosa biofi lm in a longterm (3 day) study with the salicylic acid containing polymers was demonstrated and a pathway was postulated using P. aeruginosa pMHLAS, containing a fl uorescent reporter gene which involved inhibition of the las quorum sensing system [53] . In another study, a clear difference was seen between bacterial strains that form biofi lms at the air -liquid interface (top -forming) and those that form at the surface -liquid interface (bottom -forming).…”
Section: Salicylate -Based Polyanhydridesmentioning
confidence: 99%
“…Alternative antimicrobial coatings such as salicylic acid, 11 quaternary ammonium compounds, 12 and chlorhexidine 13 have also been trialed. However, in many cases development of microbial resistance 14 makes these forms of therapy short-lived.…”
mentioning
confidence: 99%